Pergeseran Identitas Budaya Komunitas Supporter Surabaya di Instagram - Ririn Puspita Tutiasri; Ade Kusuma (Kanal: Jurnal Ilmu Komunikasi, 2017)
Bonek is called to support the football team Persebaya Surabaya. Bonek image could not be separated from the abbreviation of the word itself, namely "bondo nekat" or dare to do anything to support the team despite not having capital (material). This research explained the shift of group identity shown by Bonek Kampus community through instagram @bonekcampus27 account. The object of this research was text image or writing in the form of caption, which is posted in account @bonekcampus27. Data analyzed Roland Barthes semiotics. The results showed that the figure of Bonek as a supporter of football club Persebaya Surabaya had a different image or stereotype with other supporters. Bonek was no longer labeled with a frightening appearance or behavior that threatens the safety and security of society, but shifts to bonek as a supporter who sincerely supports the success and progress of the team Persebaya Surabaya, had ethics and uphold sports values.